2003
DOI: 10.1074/jbc.m207577200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Promotes a Distinct CD4 T Cell Activation State Characterized by the Production of Interleukin-17

Abstract: Interleukin (IL)-17 is a pro-inflammatory cytokine that is produced by activated T cells. Despite increasing evidence that high levels of IL-17 are associated with several chronic inflammatory diseases including rheumatoid arthritis, psoriasis, and multiple sclerosis, the regulation of its expression is not well characterized. We observe that IL-17 production is increased in response to the recently described cytokine IL-23. We present evidence that murine IL-23, which is produced by activated dendritic cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
1,247
5
21

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,650 publications
(1,342 citation statements)
references
References 34 publications
51
1,247
5
21
Order By: Relevance
“…Therefore, we hypothesized a role of TLR2-expressing LC for polarizing Th17 immune responses and investigated their potential to induce IL-17. In this study we show that peptidoglycan (PGN)-stimulated MoLC secreted IL-6, IL-1b, IL-23, and TGF-b Blocking of TLR2 by specific antibody inhibited IL-6, IL- To date, IL-6 and TGF-b are prominent cytokine candidates for polarization of naive Th cells into Th17 cells, whereas IL-23 is discussed for Th17 outgrowth of already differentiated cells [5][6][7]26]. In human skin, among other cytokines IL-6 is produced by LC upon microbial stimulation by PGN and other TLR2 agonists [23].…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, we hypothesized a role of TLR2-expressing LC for polarizing Th17 immune responses and investigated their potential to induce IL-17. In this study we show that peptidoglycan (PGN)-stimulated MoLC secreted IL-6, IL-1b, IL-23, and TGF-b Blocking of TLR2 by specific antibody inhibited IL-6, IL- To date, IL-6 and TGF-b are prominent cytokine candidates for polarization of naive Th cells into Th17 cells, whereas IL-23 is discussed for Th17 outgrowth of already differentiated cells [5][6][7]26]. In human skin, among other cytokines IL-6 is produced by LC upon microbial stimulation by PGN and other TLR2 agonists [23].…”
Section: Introductionmentioning
confidence: 84%
“…Th cells producing IL-17 (Th17 cells) are a distinct subset of effector cells that differentiate from naive T cells in response to IL-6 and TGF-b [25,26], whereas IL-23 serves as an important factor to expand previously differentiated Th17 cell populations and gd T cells [27,28]. Our data showed that C5a significantly increased IL-17 production by T lymphocytes in the presence of DC, while it had no influence on IL-17 production from T lymphocyte when DC were absent.…”
Section: Discussionmentioning
confidence: 99%
“…Since IL-23 regulates the production of both IL-22 [4] and IL-17 [3], we further examined the effect of exogenous IL-23 on susceptibility to Con A-induced hepatitis. In WT mice, exogenous IL-23 significantly increased the serum levels of both IL-22 and IL-17 as expected (Fig.…”
Section: Il-17-deficient Mice Show Ameliorated Hepatitis and Exogenoumentioning
confidence: 99%
“…IL-23 acts on memory-type cells [2] and induces the production of IL-17 [3] and IL-22 [4]. Moreover, IL-23 is an essential factor in the survival and expansion of Th17 cells [5], which produce cytokines including IL-17, IL-17F, IL-22, IL-6 and TNF-a [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation